Using Mac OS X Snow Leopard - Johnson, Yvonne (Que, 2010)
"Using Mac OS X Snow Leopard brings you over 65 video tutorials detailing everything from desktop configuration and Web browsing to using Widgets and making your own DVDs. Watching these videos is the fastest way to get comfortable with the newest features of Snow Leopard! Topics covered include passwords and preferences; user account control; support resources and file management; managing mail and editing photos; importing video and playing music, and much, much more!"--Resource description page.